2006
DOI: 10.1007/s00586-006-0066-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost and utilization of blood transfusion associated with spinal surgeries in the United States

Abstract: IntroductionIn general surgery and in spinal surgery, allogeneic blood transfusions (ABT) have been related to increased post-operative complications [12,13, 37, 39]. As such, reduction in ABT is a high priority in spinal surgery. Recently, techniques to reduce the need for ABT during spinal surgery have surfaced in the orthopedic surgery literature.Understanding the risk factors and costs associated with ABT can help with the discovery of new costeffective methods to reduce its burden. Several possible method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 48 publications
3
27
1
3
Order By: Relevance
“…Comparable to the findings by Blanchette et al 30 , resource utilization on the whole is similar in the US and Belgium; however differences persist. The length of inpatient hospital stay is more than twice as long in Belgium than the US.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Comparable to the findings by Blanchette et al 30 , resource utilization on the whole is similar in the US and Belgium; however differences persist. The length of inpatient hospital stay is more than twice as long in Belgium than the US.…”
Section: Discussioncontrasting
confidence: 61%
“…A recent population-based study of inpatients in the US who have undergone spinal surgery described utilization and costs of spinal surgery transfusion services only to discover that transfusion reduction techniques were not widely utilized 30 . There were no studies found that described transfusion utilization and cost in Belgium.…”
Section: Introductionmentioning
confidence: 99%
“…The increased blood loss may lead to transfusion use during the perioperative setting that can carry associated morbidity. Transfusions of even one unit of blood in surgical patients are associated with increased risk of wound complications, postoperative infections, renal dysfunction, pulmonary complications, systemic sepsis, composite morbidity, and postoperative length of stay [6,10,12,16,21,29,32,33,43]. The risks of transfusion must be balanced with the need to maintain appropriate levels of perfusion to end-organs and the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Safe and effective pharmacological blood conservation strategies are needed, as the risks and costs associated with allogenic blood transfusions continue to increase (7,8). Such pharmacological treatments for hemorrhage are particularly important in developing nations, where blood banking facilities are limited, the risk of blood-borne infection is high, and the number of trauma-related deaths is rapidly rising (9).…”
Section: Introductionmentioning
confidence: 99%